PERBANDINGAN HASIL PENETAPAN KADAR VITAMIN C MANGGA DODOL DENGAN MENGGUNAKAN METODE SPEKTROFOTOMETRI UV-Vis DAN IODOMETRI - Karinda, Monalisa; Fatimawali, Fatimawali; Citraningtyas, Gayatri (PHARMACON, 2013)
ABSTRACT Vitamin C is one of the nutrients that role as antioxidant and effectively overcome the free radicals that can damage cells or tissue. Fruit is a good source of vitamin C, such as the mango fruit. This study aimed to determine the levels of vitamin C in the mango fruit using UV-Vis spectrophotometry method and Iodimetry method, and compare the results of both methods. Samples were identified as ripe mango. In this study, the levels of vitamin C were analyzed by using UV-Vis spectrophotometry and Iodimetry. The results of the analysis of vitamin C in the mango dodol by using UV-Vis spectrophotometry is 15.88 g/100g, whereas the content of vitamin C by using Iodimetry was 3.5 g/100g. From these results, showed the levels of vitamin c by using the spektrofotometry uv-vis method is higher than the iodimetry method. Keywords: Vitamin C, mango, UV-Vis Spectrophotometry, Iodimetry.